Micro and smart systems : technology and modeling - Ananthasuresh, G.K (John Wiley and Sons, 2012)
"This first undergraduate-level textbook on microsystems and smart systems makes a burgeoning area of professional practice accessible to course teaching. It is based on a course introduced at VTU in India in 2009, which has already been taught to nearly 1000 students. Practical examples and exercises will set this book apart from the professional reference books currently in use as texts on the subject"--